Communicating Democracy: The Discourse of Political Leaders of the Baltic States (Parliamentary Studies, 2022)
The term democracy, which is a compound noun consisting of two Greek words demos and kratos and stands for people and power, recently has acquired yet another meaning, that of a way of governing the state based on the will of people. Communication is one of the key elements of a democratic polity; whereas language serves as one of the key forms in the realisation of political communication. The public communication of political leaders of the Baltic States, specifically, the presidents as representative leaders, during the tree decades of restored independence has been focused on the idea of democracy, emphasizing the thematic areas of ‘returning to the West,’ ‘returning to Europe,’ and ‘returning to democracy’ as central elements of national identities of those states. The paper offers a corpus-assisted critical discourse analysis of presidential speeches given by the presidents of Estonia, Latvia and Lithuania during the three decades of independence with the focus on the linguistic representation and discursive construction of democracy.
Keywords: Baltic States; democracy; corpus-assisted critical discourse analysis; presidential discourse